THE ADVENTURES OF PATRIMONITO - UNESCO (SCHOOL SCIENCE, 2010)
One of the themes of the International Year of Biodiversity is Education. UNESCO’s World Heritage Education Programme has developed a series of short, animated cartoons for schools which depict the adventures of a character called Patrimonito, a heritage guardian whose name means‘ small heritage’ in Spanish.